Pengadilan HAM dan Yurisdiksi Pengadilan Internasional - sefriani sefriani (Jurnal Hukum IUS QUIA IUSTUM, 2001)
This article attempts to describe establishment and jurisdiction of several international court that their duty related with thecrime ofhumanity, war crime, andgenocide especially the international criminal court (ICC). This article also attemts to respons what will be happened if the Indonesian ad hoc tribunal for the serious human right violation in East Timor failed realized itsduty. Isittrue thattheaccused will be bring tojustice byICC? is it ICC has jurisdiction over serious human right violation In East Timor? How aboutwith Semanggi I and II also Tanjung Priok cases? That questions wiifbe respons bythis article.